Pengaruh Lingkungan Belajar dan Media Pembelajaran Terhadap Minat Belajar Mahasiswa Pendidikan Ekonomi Universitas Sebelas Maret - Yustina Dianti; Mintasih Indriayu; Dewi Kusuma Wardani (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This research aims to determine: (1) the influence of the learning environment on student’s learning interest, (2) the influence of the learning media on leearning interest, (3) the simultaneous influence of the learning environment and learning media on the learning interest of Economics Education students at Sebelas Maret University. This research is a quantitative decriptive approach involving Economics Education students from the cohorts of 2020, 2021, 2022, and 2023. The sampling technique utilized in this research was probability sampling, specifically proportionate random sampling. Data analysis was conducted using multiple linear regression analysis. The result of this research are as follows: (1) there is a positive abd significant influence of the learning environment on learning interest. (2there is a positive and significant impact of learning media on learning interest. (3) there is a positive and significant influence of both the learning environment and learning media simultaneously influence the learning interest of Economics Education students at Sebelas Maret University.